Taoist way of a balanced exercise training cocktail for the management of primary hypertension in older persons - Xiao, Wensheng; Wang, Bihan; Bai, Xiaorong; Tang, Shouyong; Zhang, Yang (Frontiers in Public Health, 2023)
High blood pressure is the world's leading risk factor for mortality, affecting nearly half of the global population aged 50-79 years. Physical inactivity is one factor contributing to the prevalence of hypertension. This paper discusses a new concept for the management of hypertension in older persons. We are inclined to fade the current guidelines used in China, the United States, and Europe.Although demonstrating irrefutable benefits for blood pressure regulation, the guidelines fail to address the need to incorporate balance exercises, which are crucial for mitigating the risk of falling.We address three pressing questions regarding the efficacy of various combinations of exercise modes for blood pressure regulation, alongside providing an overview of balance exercises. At the core of our concept, we explicate the challenges inherent in addressing the global pandemic of physical inactivity and hypertension in regular socioeconomic people. No guidelines could change the state of inactivity by jumping between zero and all things, where "zero" symbolizes conditions such as physical inactivity and hypertension, and the concept of "all things" encompasses the ideals of an active lifestyle and healthy aging. We advocate a Taoist way, "zero-one-all things", where "one" in this context refers to an inclusive and culturally diverse exercise training cocktail. The Tao guides us to illuminate an ancient way of overcoming the physical inactivity associated diseases in the present day.